2020
DOI: 10.18502/kss.v4i7.6844
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Game-Based Learning – Learning in Modern Education

Abstract: The experiential learning process is a relevant method used to enhance understanding of the field and the critical thinking skills of learners. Futher more, technological developments improve students ' learning needs. In this case, learners are required to be able to learn and work dynamically by combining the concept of critical thinking and the way of life as demand for the 21st century. Therefore, dynamic learning and the ability to improve the cognitive and collaborative abilities of learners in their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
1
16
0
1
Order By: Relevance
“…Studies showed that the use of game-based learning might improve student-learning outcomes (Brezovszky, 2019;Wardoyo, DwiSatrio, Ma'ruf, 2020). Digital games had certain advantages and values for cognitive memory-based learning (Wu et al, 2020).…”
Section: Game-based Learning and 21 St Century Pedagogymentioning
confidence: 99%
“…Studies showed that the use of game-based learning might improve student-learning outcomes (Brezovszky, 2019;Wardoyo, DwiSatrio, Ma'ruf, 2020). Digital games had certain advantages and values for cognitive memory-based learning (Wu et al, 2020).…”
Section: Game-based Learning and 21 St Century Pedagogymentioning
confidence: 99%
“…Using the interpretation of the effectiveness of N-Gain with percentage categories Table 2 (Wardoyo et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Berdasarkan analisis situasi secara umum, permasalahan yang dihadapi oleh pengelola wisata Bedengan yakni pengelola belum memiliki kemampuan dalam Penanganan Gawat Darurat (PGD), bentuk-bentuk permainan outbound untuk bermacam-macam kategori umur, serta penjelasan tujuan dari permainan dilakukan. Hal ini sejalan dengan bahasan penelitian yang menyatakan pentingnya permainan dalam menstimulus pengetahuan (Grivokostopoulou et al, 2019;Satrio et al, 2020;Wardoyo et al, 2020). Selain itu, taman wisata Edukasi Bedengan bisa dikatakan belum dikelola untuk kegiatan pembelajaran alam berbasis permainan.…”
Section: Pembahasanunclassified